2002
DOI: 10.1051/forest:2002046
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of genomic regions controlling microdensitometric parameters of wood characteristics in hybrid larches

Abstract: -The use of wood quality components in forest trees selection is hampered by long delays before phenotypic evaluation. Marker-assisted selection opens new possibilities since selection becomes feasible even before trait expression. In the present study, we have analysed 224 13-year-old hybrid larches derived from eight progenies from a single female parent in order to localise genomic regions controlling several wood traits. Traits were assessed on radial cores by microdensitometry, a method that provides esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(14 reference statements)
1
6
0
2
Order By: Relevance
“…The number and effects of detected QTLs that were observed concurs with previously reported QTL studies for growth and wood quality traits in several species, particularly those dealing with smaller sample sizes (Bradshaw and Stettler 1995;Grattapaglia et al 1996;Wu 1998;Yoshimaru et al 1998;Sewell et al 2000Sewell et al , 2002Arcade et al 2002;Markussen et al 2003). We note that many of these studies report clustering of QTLs for related and unrelated traits.…”
Section: Qtls and Qtl Effectssupporting
confidence: 90%
See 1 more Smart Citation
“…The number and effects of detected QTLs that were observed concurs with previously reported QTL studies for growth and wood quality traits in several species, particularly those dealing with smaller sample sizes (Bradshaw and Stettler 1995;Grattapaglia et al 1996;Wu 1998;Yoshimaru et al 1998;Sewell et al 2000Sewell et al , 2002Arcade et al 2002;Markussen et al 2003). We note that many of these studies report clustering of QTLs for related and unrelated traits.…”
Section: Qtls and Qtl Effectssupporting
confidence: 90%
“…In conifers, recent studies have identified several QTLs of major effect and, in some cases, their temporal and spatial interactions (Byrne et al 1997;Sewell et al 2000Sewell et al , 2002Jermstad et al 2001a, b;Arcade et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…[19,34], Pinus pinaster [33], Pinus taeda [7,37], Pinus radiata [26], Pinus sylvestris [31], Larix spp. [2] and Populus spp. [5].…”
Section: Introductionmentioning
confidence: 99%
“…Our objectives were twofold: (1) to identify the genomic regions involved in the variability of wood quality components using a QTL approach and (2) to test if these regions corresponded to the location of candidate genes involved in the biosynthesis of wood.…”
Section: Introductionmentioning
confidence: 99%
“…Wood property quantitative trait loci (QTLs) have been identified in many forest tree species, attesting the existence of major gene effects controlling part of the variation of wood and its end‐use properties (Bradshaw & Stettler, 1995; Grattapaglia et al ., 1996; Kumar et al ., 2000; Lerceteau et al ., 2000; Arcade et al ., 2002; Moran et al ., 2002; Neale et al ., 2002; Brown et al ., 2003; Markussen et al ., 2003). Co‐localizations of QTLs and candidate genes (Moran et al ., 2002; Brown et al ., 2003; Chagné et al ., 2003) have also been reported.…”
Section: Introductionmentioning
confidence: 99%